SEGMENTASI MIKROFILARIA UNTUK DIAGNOSIS PENYAKIT KAKI GAJAH BERBASIS CITRA MIKROSKOPIS - Izzati Muhimmah; Silvia Nurul Fata; Novyan Lusiyana (Teknoin, 2016)
Elephantiasis is a chronic disease (chronic) that could attack humans and animals, and causes a permanent disability if not immediately given treatment. Some filaria species in Indonesia include Wuchereria bancrofti, Brugia malayi, and Brugia timori. The main goal in the early treatment of people with this disease is to eradicate parasites or larvae that develop in the patient's body, so that the level of transmission can be reduced. To help identifying the type of microfilaria that develops in the body of the patient, the authors took the initiative to create a computer-assisted program that is expected to recognize microfilaria on peripheral blood preparation. In this case, there are 4 stages of analysis of the microscopic images, namely image readings, preprocessing, segmentation, and shape analysis to identity the microfilaria.